Boletus littoreus (Boletaceae, Boletales), a new species with a white basidioma from Hainan, China - Yang, Yu-Ying; Xu, Chang; Wang, Yi; Li, Le; Yuan, Lang-Xing; Zhao, Fu-Wei; Zeng, Nian-Kai (Phytotaxa, 2022)
Boletus littoreus (Boletaceae, Boletales) is described as a new species from tropical China based on morphological and molecular evidence from the nuclear ribosomal large subunit RNA (28S), the translation elongation factor 1-α gene (TEF1), and the RNA polymerase II second largest subunit gene (RPB2). It is morphologically characterized by white basidiomata, a stipe without reticulations, a pileipellis composed of elliptic-fusiform to subglobose, sometimes filamentous, chains of hyphae, and is associated with trees of Dipterocarpaceae. An illustrated morphological description is provided along with comparison to related and similar species.